Monitoring Of Household Electricity Usage Based On The Internet Of Things - Fatin, Muhammad Hanif; Nasron, Nasron; Sarjana, Sarjana; Saputra, Muhammad Renaldy (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
The increasing demand for energy efficiency in the digital era has accelerated the adoption of Internet of Things (IoT)-based technologies in household electricity management. This study presents the design and implementation of an IoT-based real-time electricity monitoring system using the ESP32 microcontroller and PZEM-004T sensor, integrated with the Blynk application for remote access. The system measures voltage, current, power, energy consumption, and cost, displaying data on both an LCD and a mobile interface. Experimental testing involved household appliances such as fans and rice cookers under individual and combined usage, with measurements taken at 15-minute intervals. The results demonstrated strong agreement between theoretical calculations and real-time data, with the measured values slightly higher due to the dynamic nature of electrical loads. The system achieved a low average error rate of 0.17%, with a maximum error of 0.30%. These findings confirm the accuracy and reliability of the system, supporting its potential for enhancing user awareness, improving billing precision, and contributing to sustainable energy use in smart home applications.